Analisis Pengelolaan Mahasiswa Pekerja Paruh Waktu di Usaha Kuliner - Julio Mak; Syelin Angelica Manorek; Pathericio Mokoginta; Josia Aditya Pua; Abraham Leslie Petir Lelengboto (LPPM STIEM BONGAYA, 2026)
Abstract: Human resource management poses a significant challenge for culinary businesses that rely on students as part-time workers, particularly in balancing academic demands with business operational requirements. This study aims to analyze the management of student part-time workers at Kedai XXXX using the Theory of Constraints (TOC) as the theoretical framework. A qualitative research method with a case study approach was employed. Data was comprehensively collected through interviews, observations, and documentation. The informants consisted of an operational manager and three student part-time workers. The data were then analyzed using thematic analysis guided by the five focusing steps of the Theory of Constraints. The findings identify two main themes: Work–Study Balance and Working Environment. The results indicate that mental and physical fatigue, as well as academic priority, constitute the primary constraints affecting operational stability. Conversely, financial motivation, character development, a healthy work environment, and managerial intervention play important roles in sustaining the performance of student part-time workers. This study recommends implementing an adaptive scheduling system to accommodate students’ academic needs while maintaining the operational effectiveness of culinary businesses. Keywords: Student, Part-time worker, Work-Study Balance, Working Environment